Tourism to serve culture: the evolution of an Aboriginal tourism business model in Australia. Issue 4 (19th February 2020) - Scherrer, Pascal
Abstract : Purpose: This paper aims to track the evolution of an innovative Aboriginal tourism business model with deliberate social and community enterprise objectives in a remote setting. Design/methodology/approach: It adopts an in-depth exploratory case study approach to discover key characteristics of an emerging tourism enterprise. The qualitative data sources include publically available planning, promotional and organizational materials, in-depth interviews with key informants and on-site observations. Yunus et al.'s (2010) social business model provides the framework for the case analysis. Findings: Findings highlight the gradual deepening of Indigenous engagement – from simply providing a place for a non-Indigenous tourism business – to running a fully Indigenous-controlled, staffed and themed on-country tourism business. Complementing existing non-Indigenous tourism experiences reduced the need for start-up infrastructure and market recognition, thus reducing business risk for the Traditional Owners. Despite substantial changes in the business structure in response to political and maturation factors, the core motivations seemed to remain strong. The business model facilitates value creation to stakeholders in varying ways. Research limitations/implications: The contextual nature of Indigenous tourism reflects limitations of qualitative case study methodology. Practical implications: The resulting business model provides a contextually appropriate structure to engage in tourism for achieving cultural and societal goals. It mitigates against the identified risk of low market demand for Indigenous tourism experiences by connecting with established non-Indigenous tourism products, while also allowing for product offering independent thereof. Social implications: Social benefits are high and have potential for replication in similar contexts elsewhere. Originality/value: The paper contributes to the emerging research on culturally appropriate business models in Indigenous tourism contexts and validates a strategy to overcome low demand. It offers a model that for the tourist facilitates a sustainable experience which enables co-production while for the hosts fosters community resilience, intergenerational learning and improved livelihoods. The case highlights opportunities for further research into the interrelationship, dependencies and thresholds between the social and economic profit equations, particularly in the context of the culture conservation economy. Abstract : 旅游服务文化：澳大利亚原住民旅游商业模式的演变 目的（不超过100个字）: 本文追踪了以社会及社区企业为主的偏远地区的创新原住民旅游商业模式的演变。具 设计/方法/方法（不超过100个字）: 本研究采用深入的探索性案例研究方法来发现新兴旅游企业的关键特征。定性数据包括可公开获得的计划, 促销和组织资料, 与主要信息提供者的深入访谈以及现场观察。 Yunus等人（2010）的社会商业模型提供了案例分析的框架。 结果（不超过100个字）: 调查结果凸显了土著人参与度的逐步深化–从简单地为非土著人旅游业务提供场所, 到经营完全由土著人控制, 配备人员以及进行主题化的国家旅游业务。丰富现有的非土著旅游体验, 可以减少对启动基础设施和市场认可的需求, 从而降低了传统业主的业务风险。尽管由于政治和成熟因素, 业务结构发生了重大变化, 但核心动机似乎仍然很强。研究得出的商业模型通过各种方式促进了利益相关者的价值创造。 研究限制/含义（限制100个字）: 土著旅游的性质反映了定性案例研究方法的局限性。 实际含义（限100个字）: 本研究中的商业模型为通过旅游业实现文化和社会目标提供了一种适当情景下的结构。通过与成熟的非土著旅游产品建立联系, 目的地缓解了针对土著旅游体验的低市场需求风险。同时本文之方案还为其独立旅游产品开发提供了可能。 社会影响（限100个字）: 此商业模式的社会效益很高, 并且有可能在其他类似情况的地方进行复制。 创意/价值（限100个字）: 本文为土著旅游背景下文化相关的商业模式的新兴研究做出了贡献, 并提出并验证了克服低需求的策略。它为游客提供了一种可持续发展的体验模式, 使人们可以实现体验共创, 同时为居民提供的模式则可以提高社区的适应能力, 代际学习机会和改善生计的途径。该案例强调了进一步研究社会与经济利益之间的相互关系, 依存关系和阈值的机会, 尤其是在文化保护经济的背景下。 关键词: 土著旅游, 价值创造, 共创, 文化保护经济, 社会企业, 金伯利地区 Abstract : Turismo para servir a la cultura: la evolución de un modelo de negocio de Turismo Aborigen en Australia Objetivo (límite de 100 palabras): Este documento analiza la evolución de un modelo de negocio del Turismo Aborigen innovador, con un objetivo social común y empresarial determinado en un entorno remoto. Diseño/metodología/enfoque (límite de 100 palabras): Adopta un enfoque profundo y exploratorio de estudio de caso para descubrir las características claves de una empresa turística emergente. Las fuentes de datos cualitativos, incluyen materiales de planificación, promoción y organización de acceso público, así como entrevistas en profundidad con informantes claves y observaciones in situ. El modelo de negocio social de Yunus et al. (2010) proporciona el marco para el análisis de casos. Resultados (límite de 100 palabras): Los hallazgos destacan la profundización gradual de la implicación indígena, desde proporcionar simplemente un lugar para un negocio de turismo no indígena, hasta un total control de la gestión del negocio turístico con personal y temática indígena. Complementando las experiencias existentes de turismo no indígena, se redujo las necesidades iniciales de infraestructuras y reconocimiento del mercado, disminuyendo así el riesgo comercial para los Propietarios Tradicionales. A pesar de los cambios sustanciales en la estructura empresarial que los factores políticos y de maduración provocan, las motivaciones centrales parecían mantenerse fuertes. El modelo de negocios facilita la creación de valor a las partes interesadas de diversas formas. Limitaciones/implicaciones de la investigación (límite de 100 palabras): La naturaleza contextual del turismo indígena refleja las limitaciones de la metodología de estudio de caso cualitativa. Implicaciones prácticas (límite de 100 palabras): El modelo de negocio resultante proporciona una estructura contextualmente apropiada para la implicación de las comunidades indígenas en el turismo y poder lograr objetivos culturales y sociales. Mitiga el riesgo identificado de la baja demanda del mercado de experiencias de turismo indígena, al relacionarse con productos turísticos no indígenas establecidos, al tiempo que permite la oferta de productos independientes de los mismos. Implicaciones sociales (límite de 100 palabras): Los beneficios sociales son altos y tienen potencial de replicación en contextos similares en otros lugares. Originalidad/valor (límite de 100 palabras): El documento contribuye a la investigación emergente sobre modelos de negocio apropiados, desde el punto de vista cultural, en contextos de turismo indígena y valida una estrategia para superar la baja demanda. Ofrece un modelo que por un lado, facilita al turista una experiencia sostenible permitiendo la coproducción, mientras que para los anfitriones, fomenta la resiliencia comunitaria, el aprendizaje intergeneracional y mejora los medios de ganarse la vida. El caso resalta las oportunidades para una mayor investigación sobre la interrelación, las dependencias y los límites entre la ecuación de beneficios sociales y económicos, particularmente en el contexto de la economía de preservación cultural. Palabras clave: Turismo indígena, creación de valor, coproducción, economía de preservación cultural, empresa social, región de kimberley Tipo de papel: Trabajo de investigación